Biblia i nadzieja na jej dobre tłumaczenie - Wysocki, Marcin (Vox Patrum, 2018)
In the above article, based on the correspondence of St. Jerome and St. Augustine, there has been shown how these two outstanding the Bible experts, translators and interpreters understood the principles used in its translation. In three parts – entitled: Work, Man, Way – the importance and significance of the Bible and its translations, above all the Septuagint, the tasks and features of the man who translates, the methods and ways of translating were shown. Both of them in their letters indicated: the necessity of an exceptional and proper approach to the Holy Scriptures, a good preparation of the translator and the use of a method that would be appropriate to the translated piece: in the case of the Bible – a beautiful translation preserving the arrangement of the words of the inspired Scriptures; and in the case of non-canonical pieces – expressing the thoughts using the rules of the language into which the work is translated.